(untitled) (International Conference on Modern Science and Scientific Studies, 2025)
Destruction of biological objects represents the first stage of an experiment and may include: a) physical; b) chemical (biochemical) destruction of cells or whole organisms. Physical methods are most often used to destroy cells. In this case, the destruction of an object used to be carried out with the use of a mortar and pestle (kneading), then there appeared devices that crush these objects [18,19,20].